2015
DOI: 10.1177/0957650915581313
|View full text |Cite
|
Sign up to set email alerts
|

Flow measurement and simulation of a radial inlet for centrifugal compressor

Abstract: This paper presents an experimental and numerical research on the internal flow of a typical radial inlet for centrifugal compressor. Detailed flow measurements were carried out with five-hole probes, consisting of 106 sampling holes and 2178 measuring points. Automatic calibrating and measuring systems, which made the probe calibrations, measurements and data acquisitions controlled by computer, were developed and used to accelerate the flow measurements. Since separations and vortices in the radial inlet wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Koch [13] and Flathers [14,15] added shunt vanes to the RIC and found that the flow loss increased but the outlet uniformity improved. Han [16][17][18] measured the flow field in the RIC in detail and found that the large number of vortexes generated by airflow and flow separation were the core reasons for flow loss and outlet distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Koch [13] and Flathers [14,15] added shunt vanes to the RIC and found that the flow loss increased but the outlet uniformity improved. Han [16][17][18] measured the flow field in the RIC in detail and found that the large number of vortexes generated by airflow and flow separation were the core reasons for flow loss and outlet distortion.…”
Section: Introductionmentioning
confidence: 99%
“…The airflow in the new RIC was more reasonable, the pressure loss was small, and the outlet flow was more uniform. Han [22][23][24][25] calculated the flow field inside the RIC and its influence on centrifugal compressor performance by numerical calculation, and found that the flow loss caused by the RIC had little influence on compressor performance, but the outlet distortion was the main reason for the deterioration of the performance of downstream components. In addition, the aerodynamic parameters of each section inside RIC were measured in detail through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Michelassi et al [21] and Pazzi et al [22] used a combination of experiments and numerical simulations to study the scale models of radial inlet chambers without the influence of downstream impellers, and the distributions of the velocity magnitude, flow angle and loss coefficient at the outlet of the inlet chamber were obtained and analyzed. Han et al [23,24] conducted a large-scale flow measurement on the main sections in a radial inlet chamber, including the inlet and outlet of the chamber, the intake channel's outlet and the spiral channel's outlet. The measurement was composed of more than 900 testing points on the four cross-sections, and the detailed distributions of the flow parameters inside the radial inlet chamber were first published in the open literature.…”
Section: Introductionmentioning
confidence: 99%